Perkembangan Siaran Radio, Televisi dan Multimedia (Internet) Bermuatan Dakwah - Erwan Efendi; Dwi Larasati; Rangga Dimas Arjuna (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Today, there has been a tremendous amount of advancement in the realm of information technology. With the help of information technology, everything is extremely simple. For instance, in the past, I would have needed to write to someone who lived far away in order to communicate with them, but with the development of information technology, I can now do so instantly. utilizing a cellphone or the internet, for instance. Here, current information technology can serve a variety of functions, including serving as a messenger for the teachings of Islam during sermons. Radio can be utilized as a da'wah media in addition to television to spread messages to a larger audience, also a radio. Keywords: information techonolgy, da’wa